Kinetic transport simulation of energetic particles. (31st March 2016) - Sheng, He; Waltz, R.E.
Abstract: A kinetic transport code (EPtran) is developed for the transport of the energetic particles (EPs). The EPtran code evolves the EP distribution function in radius, energy, and pitch angle phase space ( r, E, λ ) to steady state with classical slowing down, pitch angle scattering, as well as radial and energy transport of the injected EPs (neutral beam injection (NBI) or fusion alpha). The EPtran code is illustrated by treating the transport of NBI fast ions from high- n ITG/TEM micro-turbulence and EP driven unstable low- n Alfvén eigenmodes (AEs) in a well-studied DIII-D NBI heated discharge with significant AE central core loss. The kinetic transport code results for this discharge are compared with previous study using a simple EP density moment transport code ALPHA (R.E. Waltz and E.M. Bass 2014 Nucl. Fusion 54 104006). The dominant EP-AE transport is treated with a local stiff critical EP density (or equivalent pressure) gradient radial transport model modified to include energy-dependence and the nonlocal effects EP drift orbits. All previous EP transport models assume that the EP velocity space distribution function is not significantly distorted from the classical 'no transport' slowing down distribution. Important transport distortions away from the slowing down EP spectrum are illustrated by a focus on the coefficient of convection: EP energy flux divided by the product of EP average energy and EP particle flux.